Answer:
(x, y) = (3, -2)
Explanation:
4x + 3y = 6
-x - 3y = 3
Sum the equations vertically to eliminate at least one variable:
3x = 9
Divide both sides of the equation by 3:
x = 3
Substitue the given value of x into the equation -x - 3y = 3:
-3 - 3y = 3
Solve the equation for y:
y = -2
The solution of the system is the ordered pair (x, y):
(3, -2)
Check if the given ordered pair is the solution of the system of equations:
4 x 3 + 3 x (-2) = 6
-3 - 3 x (-2) = 3
Simplify the equalities:
6 = 6
3 = 3
Since all of the equalities are true, the ordered pair is the solution of the system:
(x, y) = (3, -2)
I hope this helped!